Adaptación de la escala de fatiga pediátrica para adolescentes Cubanos (2023)
Introduction: Fatigue is a frequent problem for both healthy adolescents and those who suffer from severe or chronic diseases. The available diagnostic instruments for this symptom are limited, being none of them adapted or validated in Spanish for the pediatric population. The fatigue scale of 10 items, which belongs to Pediatric Fatigue Bank of Items of PROMIS, is a simple and reliable instrument that assesses the report of general symptoms of fatigue which damage the normal functioning and daily work. Objective: Translate and adapt the PROMIS scale Pediatric Short Form v1.0- Fatigue 10a (from now on PFS-PROMIS) for Cuban adolescents. Methods: The Second Edition of Guidelines about Translation, Adaptation and Use of Tests proposed by the International Commission of Tests was taken as methodological referent. The following procedures were carried out: direct and inverse translation; judges' criteria to assess quality and pertinence of the translation for the Cuban context; group interview to adolescents, and pilot study to detect possible difficulties; exploration of the structure and reliability of the scale. Altogether 116 adolescents from seventh grade and 5 experts were included Results: The management of the scale collectively was feasible, signs of displeasure, discomfort or boredom were minimal, and the scale was understandable. The average time needed to answer all the items was about 4 minutes. There were no mistakes of format or content. Cronbach alpha coefficient was 0. 78, item-scale correlations were higher than 45. The exploratory factorial analysis through the Main Components Method with Varimax rotation identified 3 factors which explained 62% of the variance Conclusions: This study allowed having the Cuban version of the PFS - PROMIS to measure fatigue in the adolescent population, being the first stage in the validation of this instrument. Only one item was the same between the Cuban translation and the one carried out in the United States. This corroborates the importance of our own translation. The study of the magnitude did not confirm the supposition that the scale is unifactorial; therefore it is recommended the implementation of other procedures to check its psychometric properties in various larger samples, so as to be able to generalize its use in the Cuban context.